Contribuição dos movimentos sociais populares para a educação formal : perspectivas políticas críticas e emancipatórias - Mezadri, Neri José (2007)
The research presented was done to investigate the contributions of the popular social movements to formal education in a way that the school can help the students to construct knowledge articulated to the context of their lives and assume themselves as critical subjects. The school can contribute to the reproduction of the social relations, but also to place itself in a critical and transforming way. In this second perspective, the social movements can also contribute in this proposed way, helping to reveal some existing contradictions in society and in the schools. To be able to overcome this problem, in this research, concepts of the popular social movements, neo-liberal globalization, formal education, non-formal education, among other topics, were discussed. The experiences of the non-formal education developed by the popular social movements can contribute in a significant way to the formal education s qualification, especially in what regards to the relation between knowledge and reality and the perspective of a critical view. Along this research, some fundamental questions were discussed: what principles and pedagogical proceedings do the social movements form of which can help qualify the school educational practices? What are the possibilities of a dialog approach between the schools and the social movements? What is needed to do for this to happen? What proposals, principals and politics can result in this dialog? Due to this, the general objective of this research was to deepen the contribution of the social movements so that the school s education is able to instruct critical and transforming human beings. For this, a critical analysis of the mechanisms that regulate society and its contradictions nowadays was established, among of which the popular social movements emerged while counter-hegemonic political power. It is in this perspective that the social movements contribute with the political-pedagogical experiences and principles for the formulating of politics of formal education in a critical and liberal perspective. The research, in a bibliographical way, based itself in authors that discuss society, formal education, social movements and pedagogy that spring from social movements, among of which stand out: Boaventura de Souza Santos, Maria da Glória Gohn, Pablo Gentili, Zygmunt Bauman, Perry Anderson, Elli Benincá, Paulo Freire, Miguel Arroyo, Dermeval Saviani, Maria Teresa Nidelcoff and Roseli Caldart. Some documents about education produced by the movements, especially MST (a rural movement in Brazil in which they have no land), also served as a source of research. The dissertation is organized in three chapters. The first, Education and social movements in a globalization context , discusses the contester role of the popular social movements as to the politics defended by neoliberalism in relation to the political-economical and educational development and implemented by the government inside a perspective of the state minimum. The second, Contributions to the social movements in debate about educational politics , deepens the concept of the education in an extensive sense, known as a social practice, both formal and non-formal. The experiences of the No Land Movement (MST) and the Movement of the Affected by Barriers (MAB) were the most analyzed. In the third chapter, Social Movements and Education: putting the role of school in doubt , discusses in what measures schools can be problematic and construct relationships in solidarity and assume a critical and transforming posture. The role of school is put in doubt as a possible space for formation of illusions and assuming itself politically, overcoming a neutral pretense posture. The dialog between school and the social movements presents itself as a path to possible overcoming of dichotomy between knowledge and reality